2020
DOI: 10.2147/dddt.s255607
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Anti-Inflammatory Effect of Different Doses of Aliskiren in Rat Models of Inflammation</p>

Abstract: Objective: The present study was designed to evaluate the anti-inflammatory effects of different doses of aliskiren in two animal models of inflammation. Methodology: Sixty-six Wistar rats were allocated into five groups: the first group (six rats) was treated with the vehicle only, without induction of paw edema and granulomatous inflammation, and served as a negative control; the second group (12 rats) was allocated into two subgroups and treated with the vehicle only, with induction of paw edema and granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“… 46 Additionally, it was able to attenuate the inflammatory markers like CRP and TNF-α and this finding is in tune with other studies. 24 , 47 , 48 These outcomes could be explained depending on the fact that blocking the effects of angiotensin II is directly related to decreasing the oxidative damage and inflammatory process. 49–51 The histopathological findings of the current study were compatible with the biochemical results, where azilsartan showed pronounced protection against ethanol-induced gastric ulcer and in a dose-dependent manner and this was clearly demonstrated as an attenuation in the infiltration of inflammatory cells and reduction in the percentage of necrotic cellular debris.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Additionally, it was able to attenuate the inflammatory markers like CRP and TNF-α and this finding is in tune with other studies. 24 , 47 , 48 These outcomes could be explained depending on the fact that blocking the effects of angiotensin II is directly related to decreasing the oxidative damage and inflammatory process. 49–51 The histopathological findings of the current study were compatible with the biochemical results, where azilsartan showed pronounced protection against ethanol-induced gastric ulcer and in a dose-dependent manner and this was clearly demonstrated as an attenuation in the infiltration of inflammatory cells and reduction in the percentage of necrotic cellular debris.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of injection was 0.25 ml/20 g mice. Different dose levels of aliskiren have been tested before in experimental studies [ 18 , 19 ] . We have selected the least effective dose correlated to the clinical dose used in patients [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The right hind-paw was used as a negative control. The plethysmograph method was used on both hind paws of each group of rats to measure the anti-inflammatory activity and compare it to the control and treatment groups [ 43 , 44 ]. This was performed to maintain a constant paw volume.…”
Section: Methodsmentioning
confidence: 99%